2023
DOI: 10.1101/2023.02.02.23285396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The National Transportation Noise Exposure Map

Abstract: We describe the development and public availability of the National Transportation Noise Exposure Map with the goal of estimating population exposures to various noise levels at the census tract level in the United States. The map was created by overlaying the Bureau of Transportation Statistics' National Transportation Noise Map with 5-year block group population estimates from the American Community Survey, and aggregating exposed population estimates to the census tract level. Based on the exposure map, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Transportation is an important contributor to noise in urban areas. An estimated 94.9 million people are exposed to transportation noise levels that exceed 45 dB in the United States (Seto & Huang, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transportation is an important contributor to noise in urban areas. An estimated 94.9 million people are exposed to transportation noise levels that exceed 45 dB in the United States (Seto & Huang, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…In the U.S., different population groups may be more impacted by certain types of transportation noise. One study found that Asian populations are most impacted by roadway traffic noise, Black populations most impacted by rail noise, and Hispanic populations most impacted by aviation noise (Huang & Seto, 2023; Seto & Huang, 2023). Transportation noise may vary considerably throughout the day, evening, and nighttime hours -- especially, roadway traffic-related noise, which may be driven by the hours and directional flow of commuter traffic.…”
Section: Introductionmentioning
confidence: 99%